Restoring the 14-3-3/CRAF regulatory interaction in Noonan syndrome using molecular glues - Johanna M. Virta; Holly R. Vickery; Markella Konstantinidou; Mckenna C. Crawford; Marloes A. M. Pennings; Christian Ottmann; Luc Brunsveld; Michelle R. Arkin (Proceedings of the National Academy of Sciences, 2026)
Noonan syndrome (NS) is the most common RASopathy, a developmental disorder that derives from dysregulation of the mitogen-activated protein kinase (MAPK) pathway. NS results from modestly activating mutations in proteins throughout the pathway. Trametinib, a MEK inhibitor, has shown promising results for certain NS complications, but NS-specific therapeutic options are lacking. CRAF activity, which is governed by the adaptor protein 14-3-3, represents a key NS regulatory node that has not been exploited. When phosphorylated (p) at CRAF S259, the 14-3-3/CRAF-pS259 complex adopts an inactive conformation in which CRAF does not fully bind to RAS or to other RAFs. NS mutations in CRAF occur at residues surrounding S259 (CRAF NS ). Here, we quantify how these mutations impair 14-3-3/CRAF, both through decreased phosphorylation (64 to 97%) and decreased binding affinity to 14-3-3 (three- to >100-fold decrease). We also explore the potential of restoring homeostasis in NS using molecular glues (MGs) to enhance the 14-3-3/CRAF inhibitory complex. We report that MGs protect phosphorylation of CRAF WT -pS259 in CRAF-effector NS mutant backgrounds. They also stabilize 14-3-3/CRAF NS interactions and increase the levels of S259 phosphorylation up to 2.8-fold, leading to decreased association of CRAF with NRAS and decreased formation of the active CRAF kinase dimers. Ultimately, inhibition of CRAF activation leads to decreased phosphorylation of the downstream target ERK, similarly to trametinib, in three different NS variants (activation of the phosphatase SHOC2, CRAF S257L , and CRAF V263A ). These results reveal a potential therapeutic strategy for NS and related RASopathies. They also demonstrate the scope and limitations of stabilizing mutation-weakened complexes with molecular glues.